No Crisis but Methodological Separatism: A Comparative Study of Finnish and Danish Publication Trends between 1990 and 2009. (April 2015) - Erola, Jani; Reimer, David; Räsänen, Pekka; Kropp, Kristoffer
This article compares methodological trends in nationally and internationally oriented sociology using data from the articles of three Nordic sociological journals: one international ( Acta Sociologica ), one Finnish ( Sosiologia ), and one Danish ( Dansk Sociologi ). The data consists of 943 articles in total: 353 published in Acta Sociologica, 277 in Sosiologia and 313 in Dansk Sociologi over the period 1990–2009. We distinguish between three main types of article: those having no or very little empirical content; empirical articles applying qualitative analysis; and empirical articles applying quantitative methods. The results suggest that quantitative research is increasingly concentrated in international publishing venues, while national journals act more and more as platforms for qualitative research. In conclusion, the broader implications of these diverging publishing trends for sociological research are discussed.